The Effectiveness of Exercise Intensity on the Agility of U-13 Badminton Players - Suratman Suratman; Sugiharto Sugiharto; Setya Rahayu; Rumini Rumini (International Conference on Science, Education, and Technology, 2022)
This research is motivated by the importance of applying intensity so that exercise has high effectiveness on agility. This study aims to partially determine the effectiveness of exercise intensity on the agility of badminton players and the difference between the two. This research is an experimental study using two groups of samples obtained by matching subject designs. The population and samples used were 12 badminton athletes in the Under-13 male group. One group received moderate-intensity exercise, and the other group received low-intensity exercise. The distribution of exercise intensity was done randomly. After 16 exercises, the two sample groups were tested for agility. The research revealed that the data prerequisite test was not met, so a non-parametric quadratic model was carried out. The results of non-parametric data show that exercise using moderate intensity on the agility of U-13 badminton players has an effectiveness of 92.40%, and exercise using low intensity on the agility of U-13 badminton players has an effectiveness of 90.70%. The difference in the effectiveness of low and moderate-intensity training on the agility of Under-13 badminton players is 1.70%. An important finding in this study is that it is better to practice using moderate intensity to improve the agility of the men's Under-13 badminton players.